RASIONALISASI PENATAAN KELEMBAGAAN PEMERINTAH DAERAH - Joni Dawud (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2007)
Through local autonomy, local governments are expected to shape a rational institutionalstructure based upon local needs. However, it reveals that local government structure hasbecome more ineffective and inefficient. Having known this, necessities for structuredownsizing should be voiced to meet the real local needs.